2007
DOI: 10.1002/num.20235
|View full text |Cite
|
Sign up to set email alerts
|

Boundary‐conforming coordinates with grid line control for acoustic scattering from complexly shaped obstacles

Abstract: The current work sets forth a practical approach to numerically solve two-dimensional direct acoustic scattering problems from complexly shaped scatterers with severe singularities, such as corners and cusps. First, boundary conforming coordinates are generated. This generation is performed through an elliptic grid generator algorithm, including control of the coordinate lines. The grid line control solely depends on the initial distribution of grid points. Following the grid generation process, the initial bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…This incident wave is scattering from a region containing three cylindrical obstacles with their crosssections bounded by the following closed curves: epicycloid, astroid, and four-petal rose. Their parametric equations are given in [13].…”
Section: Numerical Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This incident wave is scattering from a region containing three cylindrical obstacles with their crosssections bounded by the following closed curves: epicycloid, astroid, and four-petal rose. Their parametric equations are given in [13].…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Finally, the values of φ(ξ, η) and ψ(ξ, η) at the interior points of the computational domain D are defined by linear interpolation along the η-curves (η = constant) and the ξ-curves (ξ = constant), respectively. Numerical experiments on several multiply connected domains with a single hole in [12,13] revealed that the desired spacing among the ξ-curves and the η-curves of the final grid is governed by these control functions. Since the control functions are defined from the initial distribution of the grid points at the physical boundaries and at the branch cut, it is this initial distribution of points which ultimately governs the spacing among grid lines.…”
Section: Bcgc Extended To Multiply Connected Regions With Several Holesmentioning
confidence: 98%
See 3 more Smart Citations